การพัฒนาตัวดูดซับโลหะหนักและสีย้อมผ้าแทนถ่านกัมมันต์เชิงการค้า: Development of Heavy Metal and Dye Adsorbents to Substitute for the Commercial Activated Carbon - Thabuot, Mallika (Asian Health, Science and Technology Reports, 2010)
This study was to compare the potential of heavy metal and hazardous dye removal from synthetic wastewater. Anthracite coal derived-activated carbon (Antracite-AC), bagasse fly ash (BFA) were used as the adsorbents, also the commercial activated carbon (Commercial-AC). The first attempt was about to determine the optimum condition in the production of activated carbon with highest iodine number from anthracite coal by physical activation process. Considered parameters were carbonization temperature, activation agent, activation time and activation temperature. The adsorption experiment was set up to decrease the heavy metal Cu2+and Ni2+, also the adsorption of BENNEFIX RED 5B dye in the wastewater was carried out. The studied variables were the absorbent size (140-200 and 20-270 mesh), the absorbent amount (40 and 100g/l), the initial concentration of heavy metal (40 and 80 mg/l) and the concentration of BENNEFIX RED 5B (125 mg/l). Results showed that the optimum condition to obtain the activated carbon was heating the anthracite coal to increase the carbon proportion at 500oC for 1 hr under nitrogen atmosphere followed by using the carbon-dioxide as the activation agent at 750oC for 1.5 hr. The resulted activated carbon has highest iodine number about 716.56 mg/g with surface area of 650 m2/g. BFA adsorbent (200-270mesh) has the poorest surface area and pore size characteristics among the group. However, it has the higher adsorption capability of Cu2+ and Ni2+ than the Commercial-AC and Antracite-AC. In the contrast, it is the worst absorbent in color adsorption. Antracite-AC (140-200mesh) showed lowest adsorption capability of heavy metal whereas its color adsorption was more superior to the others.